2013
DOI: 10.1007/s13280-013-0442-2
|View full text |Cite
|
Sign up to set email alerts
|

Narratives Can Motivate Environmental Action: The Whiskey Creek Ocean Acidification Story

Abstract: Even when environmental data quantify the risks and benefits of delayed responses to rapid anthropogenic change, institutions rarely respond promptly. We propose that narratives complementing environmental datasets can motivate responsive environmental policy. To explore this idea, we relate a case study in which a narrative of economic loss due to regionally rapid ocean acidification-an anthropogenic change-helped connect knowledge with action. We pose three hypotheses to explain why narratives might be parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…Here it has been suggested that localising the issue is key, such that it becomes closer in space, time and society as well as less uncertain for people [58]. Although this strategy has to be attempted with care, and more research is needed to explore the validity of this suggestion [59] one way to localise the issue will be through the use of narratives and stories about the impacts of OA in communities reliant on the marine environment (see [60]). OA is not as prominent in the UK as in parts of North America as there have not been significant impacts yet (although these are possible).…”
Section: Egalitarianismmentioning
confidence: 99%
“…Here it has been suggested that localising the issue is key, such that it becomes closer in space, time and society as well as less uncertain for people [58]. Although this strategy has to be attempted with care, and more research is needed to explore the validity of this suggestion [59] one way to localise the issue will be through the use of narratives and stories about the impacts of OA in communities reliant on the marine environment (see [60]). OA is not as prominent in the UK as in parts of North America as there have not been significant impacts yet (although these are possible).…”
Section: Egalitarianismmentioning
confidence: 99%
“…Experiential factors that make climate risk personal play a significant role in influencing concern [34,32]. For example, Spence et al found that experience with flooding contributed to higher levels of concern for climate change [65].…”
Section: Awareness Of Risk For Oceans and Ocean Acidificationmentioning
confidence: 99%
“…To promote action on ocean acidification in a politically conservative environment, placing it in a cost-benefit context seems to provide an opportunity to compare it with other issues as well as to connect faces of local businesspeople with the issue. Stories help personalize these issues, greatly increasing their relevance and ability to be remembered for not only environmental activism (Kelly et al, 2014), but other fields involving behavioral change such as business marketing (Escalas, 2004), public health (Hinyard and Kreuter, 2007), and philanthropy (Maclean et al, 2013). Politically liberal environments like Washington and other West Coast states seem more receptive to taking initial action on emerging science and environmental concerns as part of a broader philosophy of environmental engagement (Hoffman, 2011).…”
Section: Discussion: Emerging Themesmentioning
confidence: 99%
“…For example, communities were galvanized to action very quickly in the Pacific Northwest United States (Barton et al, 2015), when ocean acidification jeopardized the existence of the region's lucrative and culturally iconic Pacific oyster aquaculture industry. Industry leaders quickly became activists in speaking out for action on this emerging issue (Kelly et al, 2014;Barton et al, 2015). The economic and cultural importance of the aquaculture industry forced decision makers to listen and respond.…”
Section: Why Act At the Community Level?mentioning
confidence: 99%